2009
DOI: 10.1186/1475-2875-8-198
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG response to a salivary peptide, gSG6-P1, as a new immuno-epidemiological tool for evaluating low-level exposure to Anopheles bites

Abstract: Background: Human populations exposed to low malaria transmission present particular severe risks of malaria morbidity and mortality. In addition, in a context of low-level exposure to Anopheles vector, conventional entomological methods used for sampling Anopheles populations are insufficiently sensitive and probably under-estimate the real risk of malaria transmission. The evaluation of antibody (Ab) responses to arthropod salivary proteins constitutes a novel tool for estimating exposure level to insect bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
92
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 22 publications
18
92
1
1
Order By: Relevance
“…aegypti saliva because previous studies have demonstrated that the IgG response is a useful biomarker for exposure to mosquito bites. 16,33,34 Further investigations are therefore needed to establish whether the antibody response to saliva is age dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti saliva because previous studies have demonstrated that the IgG response is a useful biomarker for exposure to mosquito bites. 16,33,34 Further investigations are therefore needed to establish whether the antibody response to saliva is age dependent.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae. 34,37 The sialome of Ae. aegypti is currently being investigated by using an immuneproteomic approach to define antigenic candidates for a specific, sensitive, and reproducible biomarker of exposure to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most practical use for mosquito saliva is as a tool for surveying human exposure to mosquito bites (3). A large percentage of the world's population lives in areas where the rate of mosquito-borne disease transmission is not accurately reflected by standard entomological measures of mosquito activity (5,6). Recent efforts have aimed to improve the sensitivity of vector exposure methods by identifying mosquito-specific saliva proteins that are immunogenic following delivery via bite.…”
mentioning
confidence: 99%
“…Recent efforts have aimed to improve the sensitivity of vector exposure methods by identifying mosquito-specific saliva proteins that are immunogenic following delivery via bite. A candidate is gSG6, a protein found only in mosquitoes of the genus Anopheles that has shown promise in several laboratory and field studies (6,7). The identification of other mosquito-specific (and genus-specific) salivary immunogens should improve this epidemiological method, and published data suggest that there are other yet unidentified saliva proteins that are more immunogenic than gSG6 (8,9).…”
mentioning
confidence: 99%
“…Despite the small size of the inoculum and the fact that only minute amounts of saliva enter the host, the impact is significant as evidenced by the induction of antibody responses against saliva proteins. Although, in the specific case of mosquitoes, a few of the saliva proteins are indeed immunogenic, the resulting antibody response directly correlates with the number of mosquito bites, thus representing a useful biomarker for exposure to (potentially infectious) bites [13,14]. Although studies with West Nile Virus reveal that the mortality of mice correlates with the number of prior exposures to the mosquito [15], the successful induction of antibodies to certain saliva proteins, which neutralize their function, can protect the vertebrate host from the infection by a subsequent bite from the same vector species.…”
Section: Meeting Discussionmentioning
confidence: 99%